A Qualitative Exploration Of The Impact Of Fostering AFL Learners' Vocabulary Skills Using BBC Arabic Live News - Sathikulameen, A; Ahamedullah, M; Ali Ibrahim, A.M.; Ansari, Thameem; Vijayakumar, S (Ijaz Arabi Journal of Arabic Learning, 2024)
This qualitative study aims to analyze the impact of BBC Arabic Live on fostering vocabulary skills. The subject totaled 37 slow learners in their bachelor of art program; the Arabic department was at The New College, Chennai, India. The Experimental Group was trained for vocabulary acquisition through ten classroom activities using BBC Arabic Live. The qualitative questionnaires were given after carrying out the classroom activities. The data were analyzed using a qualitative approach. The results showed that a live BBC Arabic News classroom activity approach brought about potential changes in their vocabulary acquisition. This study applied pedagogical implications for fostering vocabulary skills through listening skills. It underscored the practical importance of student-centered approaches for honing modern Arabic vocabulary skills. Overall, the study's findings point to the potential benefits of using BBC Arabic Live in the classroom to help students learning Arabic as a foreign language acquire vocabulary. The study's findings emphasize the necessity of learner-centric and student-centered approaches to language learning, which has significant ramifications for approaches to language teaching in higher education. Future studies in this field might look at the impact of vocabulary development on other language abilities like reading and writing, or they might examine the usage of different media sources for vocabulary acquisition.